2020
DOI: 10.35630/2199-885x/2020/10/3.1
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes as a Target of Sars Cov-2 in Pathogenesis of Covid-19

Abstract: The paper considers the possible mechanism of the pathogenesis of COVID-19 caused by SARS-COV-2, associated with damage to red blood cells, which the authors attribute to the main key target that triggers a cascade of reactions leading to multiple organ failure. The paper presents morphological evidence for the presence of pathological forms of erythrocytes characteristic of various anemias in the blood vessels and parenchyma of damaged lungs of patients with COVID-19. The death of red blood cells leads to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
11
0
5
Order By: Relevance
“…Respiratory failure is the most common direct cause of death in Covid-19 patients [33,34]. Studies have reported the nuclear remnants called Howell-Jolly bodies, or seemingly fully nucleated erythrocytes in Covid-19 patients [35,36]. Nucleated erythrocytes indicate a bad prognosis and often occurs in critically ill patients in several diseases [37].…”
Section: The Erythrocyte and Virusmentioning
confidence: 99%
“…Respiratory failure is the most common direct cause of death in Covid-19 patients [33,34]. Studies have reported the nuclear remnants called Howell-Jolly bodies, or seemingly fully nucleated erythrocytes in Covid-19 patients [35,36]. Nucleated erythrocytes indicate a bad prognosis and often occurs in critically ill patients in several diseases [37].…”
Section: The Erythrocyte and Virusmentioning
confidence: 99%
“…However, other suggestion in support of the Liu and Li hypothesis is already proclaimed, in which the attack of SARS-CoV-2 to the marrow’s immature erythrocytes (contain a nucleus) is hypothesized [ 26 ]. This data has been recently substantiated by investigating COVID-19 patients’ RBCs in which deformed erythrocytes with sickled shape and vacuolization of the cytoplasm that customarily induced by viruses attack were spotted [ 27 ]. Furthermore, a very recent study put forward by an English research group has proven a direct infection of erythroid progenitors by SARS-CoV-2 at severe stages of the disease [ 28 ].…”
mentioning
confidence: 94%
“…Способность поражать внутренние органы организма даже после выздоровления, так называемый отложенный эффект ученые изучили на биологическом материале свыше 100 умерших от коронавируса пациентов [5]. В результате они сделали вывод, что вирус способен атаковать и красный костный мозг.…”
unclassified
“…«Мы предполагаем, что главной целью для вируса становится красный костный мозг, где он повреждает эндотелий, в норме регулирующий миграцию созревающих эритроцитов в кровь. Именно по этой причине с клетками иммунитета происходят «страшные вещи», а в тканях разных органов появляются мегакариоциты -очень крупные клетки костного мозга» [5].…”
unclassified
See 1 more Smart Citation